Development of Pjbl-SSI Based E-LKM on Chemical Thermodynamics Materials - Aisyah, Aisyah; Erna, Maria; Futra, Dedi (Journal of Educational Sciences, 2025)
In the 21st century, learning in higher education must be meaningful and interactive. In physical chemistry learning, students often experience difficulties because it is theoretical. Based on this, interactive teaching materials are needed to support learning and are in accordance with the demands of the times. This study aims to develop a chemical thermodynamics E-LKM based on PjBL-SSI (Project Based Learning-Socio Scientific Issue). This research was conducted at the Chemistry Education Study Program, University of Riau in the physical chemistry course. The population in this study were 5th semester chemistry education students. The sample in this study was chemistry education students. The type of research used in this study is development research with the ADDIE model. The results of the study indicate that the developed E-LKM is valid according to the material and media validator. The developed PjBL-SSI E-LKM is practical according to the physical chemistry lecturer with a very good category and the developed E-LKM is interesting according to students with a very good category.